MODELING CALL CENTER OPERATION WITH TAKING INTO ACCOUNT REPEATED ATTEMPTS OF SUBSCRIBERS - Pustova, Svitlana (Proceedings of National Aviation University (archive), 2006)
Mathematical model for call center operation analysis was developed with taking into account repeated subscribers’ attempts. The flow of repeated attempts of subscribers influences on the parameters of the quality of service of call center. On the basis of Monte-Carlo method the algorithm of statistical model of call center operation is suggested. This model makes allowance of non-exponentially distributive laws as well as exponentially distributive laws, what makes it more adequate to realistic call centers.